Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32772
|View full text |Cite
|
Sign up to set email alerts
|

Exam Wrappers, Reflection, and Student Performance in Engineering Mechanics – Part II

Abstract: FGCU). She earned a B.S. in Biomedical Engineering from Rensselaer Polytechnic Institute (RPI) in 2004 with the Rensselaer Medal award and as a member of the inaugural class of Gates Millennium Scholars. In 2011, she earned a Ph.D. in Bioengineering from Rice University. Before joining FGCU in 2015, she was a visiting Assistant Professor of Biotechnology in the Division of Science and Technology at the United International College (UIC) in Zhuhai China. She has been exploring and applying evidence-based strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The impact on exam performance and affective behavior columns highlight findings from the papers rather than give an exhaustive list of findings. Several studies did not find any significant impact on average exam scores when using exam wrappers [7,8,9,10,11,14]. We observe that every study that examined the grades of the lowest performing students reported meaningful improvements in performance on later exams for students who completed exam wrappers [3,14,17].…”
Section: Previous Studies and Efficacy Findingsmentioning
confidence: 60%
See 3 more Smart Citations
“…The impact on exam performance and affective behavior columns highlight findings from the papers rather than give an exhaustive list of findings. Several studies did not find any significant impact on average exam scores when using exam wrappers [7,8,9,10,11,14]. We observe that every study that examined the grades of the lowest performing students reported meaningful improvements in performance on later exams for students who completed exam wrappers [3,14,17].…”
Section: Previous Studies and Efficacy Findingsmentioning
confidence: 60%
“…There are several engineering and computing education studies that found no impact on student performance [7,8,9,10,11,14], while there are others that have [5,15,17], including the study described here. It would be interesting to study the factors that contribute to successful (and unsuccessful) student usage of exam wrappers [18].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Additionally, although Exam Wrappers did not seem to increase exam scores and performance; overall, having students fill out quiz and Exam Wrappers did seem to foster reflection and adjustment in most participants [5]. They encourage students to think about their study habits, the types of errors they tend to make, and the variety of ways that they are or could be engaged in the course [6]. And finally, after a year-long experiment, it was concluded that requiring students to submit homework for a grade did not improve exam performance over students who were not required to submit homework for a grade [7].…”
Section: Introductionmentioning
confidence: 99%